광주학생독립운동가 장재성 디지털 아카이브 구축에 관한 연구 - 김문희(Moonhee Kim); 장우권(Wookwon Chang) (Journal of Records Management & Archives Society of Korea, 2021)
The purpose of this study is to present a proposal to build an archive of Gwangju Student Independence activist Jang Jae-seong. The research method used for this purpose was, first, a literature study related to Jang Jae-seong. Second, the current status of records related to Jang Jae-seong, such as the National Archives of Korea and the Ministry of Patriots and Veterans Affairs, was investigated, and the types of records were presented for each collection. Third, an expert interview with Jang Jae-seong's family was conducted. As a result of the study, the Jang Jae-seong archive was designed with documentary and commentary content. In addition, a method of linking with the record-holding institution through mapping by content was suggested. Recorded content are structured so that users can receive detailed information linked to each collection through a search. Also, considering that an archive of Gwangju student independence activists has not been established so far, a plan was prepared and presented to build an archive of people involved in the incident together and provide data. 이 연구의 목적은 광주학생독립운동가 장재성 디지털 인물 아카이브 구축안을 제시하는데 있다. 이를 위해 사용된 연구의 방법은 첫째, 장재성 관련 문헌연구를 하였다. 둘째, 국가기록원, 국가보훈처 등 장재성과 관련된 기록 현황을 조사하였다. 셋째, 장재성의 가족과 전문가 인터뷰를 실시하였다. 연구결과, 장재성 아카이브는 기록콘텐츠와 해설콘텐츠로 설계하였다. 또한 기록물 보유기관과의 콘텐츠별 매핑을 통해 연계하는 방안을 제시하였다. 기록콘텐츠는 이용자가 검색을 통해 소장처별로 연결 된 상세 내용을 제공받을 수 있도록 구성하였다. 또한 현재까지 광주학생독립운동가들의 아카이브가 구축되지 않은 점을 고려하여, 해당 사건에 대한 인물들을 함께 아카이브로 구축, 데이터를 제공하는 안을 제시하였다.